It could be viral but you don't know, you have not diagnosed it: health worker challenges in managing non-malaria paediatric fevers in the low transmission area of Mbarara District, Uganda. (December 2016) - Johansson, Emily; Kitutu, Freddy; Mayora, Chrispus; Awor, Phyllis; Peterson, Stefan; Wamani, Henry; Hildenwall, Helena
Abstract Background In 2012, Uganda initiated nationwide deployment of malaria rapid diagnostic tests (RDT) as recommended by national guidelines. Yet growing concerns about RDT non-compliance in various settings have spurred calls to deploy RDT as part of enhanced support packages. An understanding of how health workers currently manage non-malaria fevers, particularly for children, and challenges faced in this work should also inform efforts. Methods A qualitative study was conducted in the low transmission area of Mbarara District (Uganda). In-depth interviews with 20 health workers at lower level clinics focused on RDT perceptions, strategies to differentiate non-malaria paediatric fevers, influences on clinical decisions, desires for additional diagnostics, and any challenges in this work. Seven focus group discussions were conducted with caregivers of children under 5 years of age in facility catchment areas to elucidate their RDT perceptions, understandings of non-malaria paediatric fevers and treatment preferences. Data were extracted into meaning units to inform codes and themes in order to describe response patterns using a latent content analysis approach. Results Differential diagnosis strategies included studying fever patterns, taking histories, assessing symptoms, and analysing other factors such as a child's age or home environment. If no alternative cause was found, malaria treatment was reportedly often prescribed despite a negative result. Other reasons for malaria over-treatment stemmed from RDT perceptions, system constraints and provider-client interactions. RDT perceptions included mistrust driven largely by expectations of false negative results due to low parasite/antigen loads, previous anti-malarial treatment or test detection of only one species. System constraints included poor referral systems, working alone without opportunity to confer on difficult cases, and lacking skills and/or tools for differential diagnosis. Provider-client interactions included reported caregiver RDT mistrust, demand for certain drugs and desire to know the 'exact' disease cause if not malaria. Many health workers expressed uncertainty about how to manage non-malaria paediatric fevers, feared doing wrong and patient death, worried caregivers would lose trust, or felt unsatisfied without a clear diagnosis. Conclusions Enhanced support is needed to improve RDT adoption at lower level clinics that focuses on empowering providers to successfully manage non-severe, non-malaria paediatric fevers without referral. This includes building trust in negative results, reinforcing integrated care initiatives (e.g., integrated management of childhood illness) and fostering communities of practice according to the diffusion of innovations theory.